THE PERCEPTION AMONG THE STUDENTS UNIVERSITI UTARA MALAYSIA TOWARDS THE IMPACT OF PART-TIME JOB ON ACADEMIC AND HEALTH PERFOMANCE - Khai Lin chong; Muhamad Syamirul Mohamad Noor (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
The study examines how local students’ academic and health performance changes as a result of their part-time jobs. To accomplish this, the study surveyed the students of the School of Technology Management and Logistics (STML), Universiti Utara Malaysia (UUM), Sintok, Kedah. The majority of the students believe their study costs are higher than expected. This caused financial strain due to price increases globally and affected STML students and living expenses in university and impacted students’ academic and health performance. Thus, this study aims to analyse the perception of part-time jobs’ impact on student academic and health performance. The researcher focused on quantitative approaches throughout the study. Around 132 students answered the online questionnaire. The study found that there are both positive and negative impacts on student working and studying on their academic and health performance. All of the hypotheses have been confirmed and accepted. The study suggests that how well time is managed between work and study will determine whether the impact is positive or negative. Part-time jobs can be a new way for students to increase their income if the time can be managed well.